If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x * ln(x + 3) + 4 = 0 Reorder the terms: 3x * ln(3 + x) + 4 = 0 Multiply x * ln 3lnx(3 + x) + 4 = 0 (3 * 3lnx + x * 3lnx) + 4 = 0 (9lnx + 3lnx2) + 4 = 0 Reorder the terms: 4 + 9lnx + 3lnx2 = 0 Solving 4 + 9lnx + 3lnx2 = 0 Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + 9lnx + -4 + 3lnx2 = 0 + -4 Reorder the terms: 4 + -4 + 9lnx + 3lnx2 = 0 + -4 Combine like terms: 4 + -4 = 0 0 + 9lnx + 3lnx2 = 0 + -4 9lnx + 3lnx2 = 0 + -4 Combine like terms: 0 + -4 = -4 9lnx + 3lnx2 = -4 Reorder the terms: 4 + 9lnx + 3lnx2 = -4 + 4 Combine like terms: -4 + 4 = 0 4 + 9lnx + 3lnx2 = 0 The solution to this equation could not be determined.
| 11w+2(3w-1)=5 | | (9y-6)(1.5)+3.5y= | | 3.50x+40=57.50 | | 7n+n=64 | | 30x^2-25x=0 | | 2(2x+3)=24 | | -2c-24=2c-12 | | 9u-5u=36 | | 5x+2=-5 | | 6-3x=14x+2 | | 13=7r-6-2 | | 8p-6(1-2p)=86 | | x+(x+2)=116 | | n+4.1n+6=-1.5(n+4.8) | | -3(4x-8)=2-4(3x-7) | | -16x^2+64x-26=0 | | 3x-8=-24 | | 8p-6(1-2b)=86 | | a+220=x-2(x+5)2 | | 8=2-5r-4 | | 38-1.7x=25+2.1x | | 3-1+(14-2)= | | -16x^2+64x-20=0 | | 5n-7=2n+14 | | n-6+4=-4 | | y=-7x-14 | | -6-7(-8-x)=x+2 | | -12=3n+3n | | 4(4-1w)=3(2w+2) | | 18x^2+42x+20=0 | | h(t)=300t-16t^2 | | 3y+12=6y |